RECONSTRUCTION OF ‘AQĪDAH-BASED MORALS: (AN ANALYTICAL STUDY OF THE THOUGHT OF FAKHR AL-DĪN AL-RĀZĪ) - Qois Azizah Bin Has (Sekolah Tinggi Agama Islam Sadra, 2023)
Today, every Muslim is expected to have a personality that can respond to the demands of religion in life. Because this ability can bring global goodness to humans. However, Muslims today are faced with a variety of causes that cause Muslim personalities to deviate and cases of behavior and this character deviation that needs to be addressed. The criminality that exists in society is certainly contrary to religious values to is commonplace and requires special attention in handling it. This article aims to convey Fakhruddīn al-Rāzī’s idea of reconstructing morals based on faith. Using the descriptive method of analysis, researchers analyzed data in the form of the concept of ‘aqīdah and morals from the perspective of Fakhruddīn al-Rāzī. Apart from that, it also discussed the concept of morals and its division, the process, and the role of morals in humans. So ‘aqīdah becomes the main basis of Muslims in determining their outlook on life in every thought, word, action, and produce commendable morals because these praiseworthy morals are proof of the primacy of human faith. ‘Aqīdah and morals have a close relationship which results in human deeds and actions. All of them will be commendable if there is continuity between nafs, ‘aql, spirit, and qalb in interpreting the human itself and the nature of the world. So, this is where the role of ‘aqīdah as a Muslim worldview in equalizing the goals of nafs, ‘aql, spirit, and qalb to achieve ḥaqīqī happiness, namely the return of humans to their Creator.